2-D Modelling of Long Period Variations of Galactic Cosmic Ray Intensity. (July 2015) - Siluszyk, M; Iskra, K; Alania, M
Abstract: A new two-dimensional (2-D) time dependent model describing long-period variations of the Galactic Cosmic Ray (GCR) intensity has been developed. New approximations for the changes of the magnitude B of the Interplanetary Magnetic Field (IMF), the tilt angle δ of the Heliospheric Neutral Sheet (HNS) and drift effects of the GCR particles have been included into the model. Moreover, temporal changes of the exponent γ expressing the power law - rigidity dependence of the amplitudes of the 11-year variation of the GCR intensity have been added. We show that changes of the expected GCR particle density precedes changes of the GCR intensity measured by the Moscow Neutron (MN) monitor by about 18 months. So ∼18 months can be taken as an effective delay time between the expected intensity caused by the combined influence of the changes of the parameters implemented in the time-dependent 2-D model and the GCR intensity measured by neutron monitors during the 21 cycle of solar activity.